Effect of Delustering Agent on Physical and Mechanical Properties of Nylon 6 - Tayebi, H.A.; Yazdanshenas, M.E.; Rashidi, A.S.; Khajavi, R.; Montazer, M. (Asian Journal of Chemistry, 2010)
Titanium dioxide is one of the most important delustering agent additives in synthetic fiber production, as nylon. Different amounts of TiO2 are used to gain various characteristics on synthetic fibers in industrial applications. In this research two types of nylon granules were processed with different amounts of TiO2 (0.30 and 0.03 %). Then, two types of yarn were created using circular shape spinneret from the mentioned granules. The effects of TiO2 on physical, mechanical, thermal and morphological properties of granules and prepared yarns were studied. Results showed that by increasing the amount of TiO2, strength of yarns decreased. Thermogravimetric analysis showed that with enhancement in the amount of TiO2, degradation temperature was decreased. The reduction in the crystalline part was the reason for this temperature variation, as it was also proved by DSC analysis. Morphology of yarns was further studied using scanning electron microscopy (SEM), which shows an increase in the amount of TiO2 on the fiber surface, by increasing the overall amount of TiO2. Results indicate the improvement in dye adsorption by increasing the amount of TiO2.